(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The report, Driving Canada: A Front Seat View of Immigration through Uber, by the organization Qissa (the Arabic word for fable or oral story-telling) in collaboration with the Canadian Museum of Immigration at Pier 21, provides a glimpse into the countless stories of people immigrating to Canada with strong skills and years of work experiences only to find they cannot get jobs in their field and ending up driving for Uber, or working in other jobs for which they are overqualified. We decided to include this report as a resource in this issue because it emphasizes the need for better recognition systems that tap into the human resources that immigrants bring to their new country. The stories in this report are heartfelt and demonstrate the narratives we hear over and over again across the world: People are not being recognized for what they know and can do; rather, they are being pushed aside and expected to find whatever work they can at minimum or barely living wages. As a resource, this report is a call to all of us to help shift the systems in each of our countries to provide better recognition of the knowledge and skills that all people have, regardless of the source of that learning, and to assist people to engage their talents in meaningful ways. Citation Qissa. (2025). Driving Canada: A front-seat view of immigration through Uber (Digital Driving Canada Report). Qissa. https://qissa.org/wp-content/uploads/2025/05/Digital-Driving-Canada-Report.pdf